Synthesis of Polysilsesquioxanes with Double-Decker Silsesquioxane Repeating Units (Journal of Scientific Research, 2016)
Polysilsesquioxanes were synthesized with end functional double-decker silsesquioxanes (DDSQ) and the polymers were characterized with 1H NMR, 29Si NMR and size exclusion chromatography (SEC). Polysilsesquioxane containing iso-butyl end capped DDSQ showed better solubility compared to that of methyl end capped DDSQ. Thermal properties investigated with TGA showed that the polymers exhibited exceptionally high stabilities in the range of 470-530°C even in both nitrogen and air atmosphere. The average residual weights of the polymers at 760°C were around 80% in the nitrogen atmosphere.